Rancang Bangun Aplikasi Penyewaan Kamera Berbasis Web Menggunakan Metode Prototype - Naratama, I Gede Wisnu Ratya; Widiantara, I Nyoman; Putra, I Putu Dyestha Kencana (Journal Informatics Nivedita, 2026)
The development of digital technology has encouraged the increasing need for photography and videography equipment among beginners, students, content creators, and freelance videographers. However, the high price of camera equipment often becomes an obstacle for users who want to produce quality visual content. This study aimed to design and develop a web-based camera rental application called RENTCAM using the Prototype method. The system was developed using HTML, CSS, JavaScript, PHP, MySQL, and Bootstrap. The Prototype method was chosen because it allows direct interaction between developers and users during the system development process. The website provides several features including login and registration, camera data management, shopping cart, transaction management, WhatsApp-based communication, and report printing. Black Box Testing was conducted on 11 main features to evaluate the functionality of the system. The quantitative testing results showed a 100% success rate for all tested system functionalities, proving that all core modules operate smoothly and meet the user's operational requirements without any errors.